Export-Led Growth Hypothesis: Empirical Evidence from Selected South Asian Countries - Kumar, Mukesh; Nargis; Begam, Azeema (Asian Journal of Economic Modelling, 2020)
The hypothesis of Export-Led Growth (ELG) asserts exports as a development approach in order to enhance the productivity of an economy targeting big international markets. However, empirical evidences based on this postulate are mixed yet contradictory. The prime objective of this paper is to validate the customary ELG hypothesis specifically for selected South Asian economies incorporating the dynamics of the panel data. In this regard, four South Asian countries-Bangladesh, India, Pakistan, and Sri Lanka have been selected. The study employs panel unit root, panel ARDL and ECM for the time span of 1991-2017. The model includes annual GDP growth, exports, imports; and foreign direct investment for the econometric estimation. The findings prove significant and positive impact of exports and foreign direct investment whereas; negative but significant impact of imports on GDP growth of South Asian countries. Nevertheless, there exists some operational and institutional glitches that obstruct the ELG process in South Asia. These include geo-political ambiguities of the region, high price ratios, low investment rates, insufficient economic infrastructure, and unfavorable regulatory settings hampering the economic growth. It is thus suggested that South Asian countries can promote market diversification broadening the product range. Besides; policies based on export promotion should be considered to enhance capacity and quality of exports in order to stimulate growth.